Design and Simulation of Two-speed Variators with Large Transmission Ratio Based on the TRIZ Theory - Du Chunkuan; Wang Xinqin; Chen Guomei; Ni Xiao (Jixie chuandong)
Aiming at the lack of speed variators with large transmission ratio for the chain cold drawing production line, on the basis of the ZSY500-50 three-stage reducer, the technical contradiction existing in the technical system is analyzed using the TRIZ theory, and the invention principles that are conducive to solving the technical contradiction are found in the contradiction matrix table. Under the inspiration of the invention principles, the 50/100 second-speed gear transmission with reasonable and compact structure is designed by adding sliding gears, improving the sliding mechanism and optimizing the shafting layout. The strength calculation of the core components and the mechanical simulation using the Ansys Workbench software show that the core components of the two-speed variator all meet the strength requirements.